Identifying appropriate concurrent engineering principles for mass housing industry in Malaysia - Mohd Noor, Mohd Zairul (2011)
The aim of the study was to identify the appropriate Concurrent Engineering principles in the mass housing industry to address the issue of quality and competitiveness. The study conducted a qualitative approach inquiring how concurrent engineering (CE) principles can help to address the issue of quality and competitiveness in mass housing industry. The research posits that selected Concurrent Engineering (CE) principles can be adopted in the mass housing industry due to its similarity in nature with its counterpart in the manufacturing sector in solving the same issue. Three cases representing different level of company structures: multi-million capital companies, medium-sized and small-scaled housing developers; were chosen as the units of analysis for purposive sampling. One respondent represented each company was interviewed with open-ended questions using the snowballing technique. These respondents were the key personnel and were considered the gatekeeper of the respective company's information. Information such as the company's mission, decision-makings or the stakeholders was elucidated to explain the issues and problems of quality and competitiveness in the mass housing industry. Primary data was obtained from literature and validated through interviews. Observations were made during visits to the case's sites, and documents, which include company profiles, records and minutes of meetings, were reviewed to supplement the data collection. The cross-case analysis using the constant comparative method was used to generate the categories. Triangulation, peer examination and member checking were used to ascertain trustworthiness of the study. The findings suggested that although some of the principles in Concurrent Engineering might appropriate in the current mass housing industry, it could not be considered as a total adoption of CE in the mass housing industry. There are several CE fundamentals that are contradicted with the current practice of mass housing industry. However, the research posits that some principles might applicable for current mass housing industry for a good practice exercise and CE might works for manufactured construction or ISS housing construction. In summary, the research contributes to the identification of Concurrent Engineering (CE) principles for mass housing industry and addressed the issue of quality and competitiveness in the mass housing industry.